2014
DOI: 10.1007/s00592-014-0675-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124a is hyperexpressed in type 2 diabetic human pancreatic islets and negatively regulates insulin secretion

Abstract: We uncovered a major hyperexpression of miR-124a in T2D islets, whose silencing resulted in increased expression of target genes of major importance for beta cell function and whose overexpression impaired glucose-stimulated insulin secretion, leading to the hypothesis that an altered miR-124a expression may contribute to beta cell dysfunction in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 38 publications
6
119
0
Order By: Relevance
“…In fact, an increase in the level of pre-miR-375 has been reported in GK rats [26] but this observation was not confirmed by an independent study [30]. A small elevation of miR-375 was also reported in islets of ob/ob and DIO mice [18,29], but changes in miR-375 expression were neither detected in other studies by microarray profiling of islets of ob/ob, db/db and DIO mice [31,32] nor in islets of T2DM human donors [21,33]. Interestingly, increased levels of miR-375 were observed in the islets of the offspring of rats fed a low-protein diet during pregnancy.…”
Section: Role Of Specific Mirnas In the Development Of β-Cells And Inmentioning
confidence: 58%
See 2 more Smart Citations
“…In fact, an increase in the level of pre-miR-375 has been reported in GK rats [26] but this observation was not confirmed by an independent study [30]. A small elevation of miR-375 was also reported in islets of ob/ob and DIO mice [18,29], but changes in miR-375 expression were neither detected in other studies by microarray profiling of islets of ob/ob, db/db and DIO mice [31,32] nor in islets of T2DM human donors [21,33]. Interestingly, increased levels of miR-375 were observed in the islets of the offspring of rats fed a low-protein diet during pregnancy.…”
Section: Role Of Specific Mirnas In the Development Of β-Cells And Inmentioning
confidence: 58%
“…In the same study, miR-21 was found to be significantly upregulated and miR-127-3p and miR-375 had a tendency to be more elevated in islets of glucose intolerant donors [51]. In other independent studies, expression of miR-375 was found to be increased in total pancreas [52] but not in isolated pancreatic islets of T2DM donors [33]. Two other miRNAs, miR-187 and miR-124a, were found to be upregulated in islets of individuals suffering from T2DM, whereas miR-7 and miR-184 were down-regulated [18,33,39,53].…”
Section: Mirna Changes In Islets Of Human T2dm Donorsmentioning
confidence: 67%
See 1 more Smart Citation
“…In pancreatic islets from T2D donors, miR124a was expressed at much higher levels compared to normal islets [54]. Overexpression of miR124a in MIN6 cells resulted in impaired glucosestimulated insulin secretion and silencing of this miRNA correlated with increased expression of predicted target genes of relevance to β-cell function, including Mtpn, Foxa2, Flot2, Akt3, Sirt1, and NeuroD1.…”
Section: Mirnas Involved In the Regulation Of Pancreatic β-Cell Functionmentioning
confidence: 99%
“…In humans, several studies have shown that miR-375 is upregulated in the pancreas or plasma of patients with T2D compared to non-diabetic individuals [51][52][53], while others found no evidence for differential expression [54] or observed decreased expression levels in individuals with impaired glucose tolerance [55]. Altered miR-375 expression has been correlated with changes in methylation status of its promoter [51,52,55].…”
Section: Mirnas Involved In the Regulation Of Pancreatic β-Cell Functionmentioning
confidence: 99%